2017
DOI: 10.1096/fj.201700156r
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor–induced pyruvate dehydrogenase kinase 1 expression enhances head and neck squamous cell carcinoma metastasisviaup‐regulation of fibronectin

Abstract: Epidermal growth factor receptor (EGFR) activation is a major cause of metastasis in such cancers as head and neck squamous cell carcinoma (HNSCC); however, whether the metabolic enzyme, pyruvate dehydrogenase kinase 1 (PDK1), mediates EGF-enhanced HNSCC metastasis remains unclear. Of interest, we found that EGF induced PDK1 expression in HNSCC. Tumor cell transformation induced by EGF was repressed by PDK1 knockdown, and the down-regulation of PDK1 expression or inhibition of its activity significantly blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Fibronectin‐binding proteins (FnBPs) in the cell‐wall of S. aureus is an important component which can bind to extracellular matrix protein fibronectin, thereafter, the FnBP‐Fn‐α5β1 integrin interaction may initiate the internalisation of S. aureus into epithelial cells and endothelial cells (Ilic et al, 2004; Josse et al, 2015). It is reported that expression of fibronectin can be regulated by FAK and EGFR signalling, the deficiency of either FAK or EGFR signalling was demonstrated to result in downregulated expression of fibronectin (Hsu, Chang, Chang, Chang, & Chen, 2017; Ilic et al, 2004). Our data showed that blocking EGFR/FAK signalling suppresses S. aureus internalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin‐binding proteins (FnBPs) in the cell‐wall of S. aureus is an important component which can bind to extracellular matrix protein fibronectin, thereafter, the FnBP‐Fn‐α5β1 integrin interaction may initiate the internalisation of S. aureus into epithelial cells and endothelial cells (Ilic et al, 2004; Josse et al, 2015). It is reported that expression of fibronectin can be regulated by FAK and EGFR signalling, the deficiency of either FAK or EGFR signalling was demonstrated to result in downregulated expression of fibronectin (Hsu, Chang, Chang, Chang, & Chen, 2017; Ilic et al, 2004). Our data showed that blocking EGFR/FAK signalling suppresses S. aureus internalisation.…”
Section: Discussionmentioning
confidence: 99%
“…In the cancer metastasis that is mediated by the interaction between X-linked inhibitor of apoptosis (XIAP) and survivin but independent of inhibition of cell death, FN expression serves a downstream signaling factor to promote the metastasis process [92]. Furthermore, FN expression has often been found to mediate various metastatic-promoting mechanisms [93][94][95][96][97][98][99][100] (Figure 1B).…”
Section: Fn Promotes Cancer Metastasismentioning
confidence: 99%
“…It had been reported that PDK1 was remarkably overexpressed in various tumors such as lung cancer [7], gastric cancer [17],glioblastoma [18], etc. [19][20][21][22][23][24][25], regulated by hypoxia-inducible factor-1α (HIF-1α) mediated [26] or Wnt/β-catenin signaling [27] and contributed to chemoresistance of ovarian cancer by activating EGFR [28]. Michelle K. Y's team had confirmed that PDK1 could promote the development of ovarian cancer especially in metastasis by modulating tumormesothelial adhesion, invasion, and angiogenesis via α5β1 integrin and JNK/IL-8 signaling [29].…”
Section: Ivyspring International Publishermentioning
confidence: 99%